1999
DOI: 10.1211/0022357991772277
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Oral Bioavailability of Albendazole in Rabbits by the Solid Dispersion Technique

Abstract: We have investigated the oral bioavailability of granules of albendazole, a drug used for treating echinococcosis in man, prepared by the solid dispersion technique. Rapid dissolution and supersaturation were observed when hydroxypropylmethylcellulose and hydroxypropylmethylcellulose phthalate were used as carriers in the solid dispersion. They inhibited the crystallization of albendazole from the supersaturated solution and maintained an amorphous state for 8 h. Gastric acidity-controlled rabbits were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 14 publications
5
54
0
Order By: Relevance
“…The results obtained indicated that apart from the HLB value, other factors such as structure and relative length of hydrophobic chains of surfactants influenced microemulsification. These results are in agreement with the results reported in literature (36,37). Cremophor EL and Tween 20 rendered effective microemulsification and were selected for further study.…”
Section: Emulsification Studysupporting
confidence: 91%
“…The results obtained indicated that apart from the HLB value, other factors such as structure and relative length of hydrophobic chains of surfactants influenced microemulsification. These results are in agreement with the results reported in literature (36,37). Cremophor EL and Tween 20 rendered effective microemulsification and were selected for further study.…”
Section: Emulsification Studysupporting
confidence: 91%
“…Moreover, increased systemic bioavailability of albendazole was reported when the drug co-administered with a fatty meal [11], fruit juice [12], cosolvent [13], or with surfactants [14].…”
Section: Albendazole (Abz) Methyl[ 5-(propylthio)-1-h-benzimidazol-2mentioning
confidence: 99%
“…22) Kohri et al also reported the supersaturated solution by dissolution of the solid dispersion systems of albendazole with hydroxypropylmethylcellulose and hydroxymethylpropylcellulose phthalate. 23) In the absorption study, AUC values well reflected the results of the dissolution studies. The mean value of AUC following the administration of 1 : 9 solid dispersion system containing 100 mg probucol was eight times larger to that following the administration of 500 mg probucol.…”
Section: Discussionmentioning
confidence: 64%